Volumetric Computed Tomography Angiography in the Evaluation of Mediastinal Fluid Collections following Congenital Cardiac Surgery - Arno A. W. Roest; Joost Roelofs; Mark G. Hazekamp; Marry E. B. Rijlaarsdam; Jacob Geleijns; Lucia J. M. Kroft (Hindawi Limited, 2013)
We present 3 patients with 4 causes of mediastinal fluid collection after congenital cardiac surgery in this extended case report. Volumetric computed tomography played an essential role in diagnosing causes and extent, relevant to subsequent management. Recent advances in volumetric computed tomography allow fast and accurate imaging of cardiovascular and extravascular structures in children with acceptable radiation dose, providing a powerful imaging tool for the evaluation of complications after congenital cardiac surgery.